“…I AM CONVINCED THAT THERE WILL BE A KABARDIAN AUTONOMOUS OKRUG AND I WILL SUPPORT THE WILL Of THE WORKERS”. DOCUMENTS AND MATERIALS ON THE WITHDRAWAL OF THE KABARDINSKY DISTRICT FROM THE MOUNTAIN ASSR IN 1921 - A. G. KAZHAROV; M. S. TAMAZOV (Кавказология, 2021)
The published documents were found in the archives of the Republic of North Ossetia-Alania. These are the materials of the meetings of the Soviet and party authorities of the Mountain Republic, which were devoted to the discussion of the problem of Kabarda's secession from the polyethnic mountain autonomy. The Kabardian problem was discussed several times by the leadership of the Mountain Republic in June 1921 before and after the congress of the peoples of Kabarda that took place this month. The minutes of the meetings have not yet been published in the published thematic collections of documents dedicated to the history of the nation-building of the peoples of the North Caucasus. The documents contribute to the understanding of the position of the statesmen of the Mountain Republic on the formation of new autonomous units and the identification of the concrete historical content of these processes. The protocols make it possible to reconstruct the process of not only the disintegration of the collective mountain statehood, but also make it possible to clarify important points in the history of its creation. Party and Soviet leaders often returned to the problems of the initial stage of the formation of the Mountain Republic. Further study of the problems of the formation of a system of national autonomies in the North Caucasus in recent times will largely depend, including on the introduction of new documents into scientific circulation and their interpretation by a wide range of researchers. In this regard, the published documents and materials are of great scientific interest.